Health Promoting School Program to Prevent Hypertension of Adolescents in Indonesia and Western - Maninggar Kayuningtyas; Ismayani Ismayani (Universitas Airlangga, 2020)
Background: Complications of hypertension causes 9.4 million of death worldwide each year. The risk factors for hypertension include heredity and environmental factors such as obesity, salt intake, physical activity, and alcohol. One-third of teenagers spent their time on school activities, so schools contribute to preventing hypertension in adolescents through Health School Program activities. Objective: to compare the health-promoting school program in Indonesia and Western in the prevention of hypertension. Method: The method used in writing this article was a literature review from 11 specific articles that were collected through google scholar, ProQuest, and SAGE pub search engines, with article inclusion criteria published in 2013-2019. Result: the review found that health promotion program in schools which was implemented in Indonesia have not been effective in preventing the emergence of risk factors for the incidence of hypertension in adolescents, compared with implementation in western. Ineffectiveness that occurs due to nutritional control patterns in adolescents in schools in the absence of regulations governing the nutritional content of student food, the lack of the teacher’s role in implementing health education due to high academic demands, and the lack of parental involvement. Conclusion: There are differences in the implementation of the health promotion program in Indonesia and the Western. The government priority for increasing the quality of live students trough health-promoting schools.